2017
DOI: 10.1097/ijg.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Segmentation Errors in the Peripapillary Retinal Nerve Fiber Layer and Macular Ganglion Cell Complex in Spectral-domain Optical Coherence Tomography Images

Abstract: Although segmentation failure was common in both RNFL and GCC scans, it was less frequently observed in GCC scans. SSI, disc area, and disease type were significantly associated with segmentation failure. Predictive performance of baseline factors for failure was poor, underlining the importance of reviewing raw OCT images before using OCT parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“… 13 22 This may be due to our broad inclusion of several different types of artifacts, as opposed to only segmentation errors, which were the focus of other papers. 15 , 17 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 22 This may be due to our broad inclusion of several different types of artifacts, as opposed to only segmentation errors, which were the focus of other papers. 15 , 17 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…However, studies thus far have shown that gender is not associated with artifact frequency, 13 , 44 and there is conflicting evidence for whether age is a significant factor. 13 , 20 , 24 , 44 , 45 Second, our patient population did not include subjects with pre-perimetric glaucoma, for whom SD-OCT measurements play an important role in management. Nevertheless, we believe that these patients are likely captured within the range of optic nerve and peripapillary RNFL characteristics defined by glaucoma and normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Segmentation is important for analysing the thickness of the retinal layer using OCT results. Although image quality is a critical factor for segmentation, ocular structural factors such as axial length, shape of optic disc, or tortuosity of retinal vessel also affect segmentation 3 , 10 , 11 . The superotemporal, inferonasal, inferotemporal, and temporoinferior sectors contain retinal blood vessels, which contribute to the structural variation of the parapapillary area.…”
Section: Discussionmentioning
confidence: 99%
“…However, artifacts during automated segmentation of the RNFL on SDOCT are not uncommon. Several studies have reported high rates of errors on segmentation of the RNFL across different SDOCT instruments 811,18,19 . Since most of the cohort studies in the literature that reported on SDOCT for glaucoma diagnosis excluded images with artifacts, the rate of segmentation errors could be substantially higher in routine clinical practice 8 .…”
Section: Discussionmentioning
confidence: 99%